Historical review of Citrus tristeza virus and its vectors in Iran - Delkhosh H.R.; Tousi N. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
This review outlines the importance of citrus industry in Iran where the different species have been grown for many centuries. Emphasis is laid on the introduction of CTV following the import of large amounts of Satsuma varieties from Japan in the 1970s. A number of surveys were carried out from 1978 to 2007 in the main citrus growing areas across the country and a low level of natural CTV transmission was determined. Aphis gossypii, A. citricola, A. craccivora, Toxoptera aurantii and Myzus persicae proved to be the most common vectors involved in CTV spread. In contrast, T. citricidus has never been reported to date.